2014
DOI: 10.1186/1129-2377-15-15
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of headache from childhood to adulthood: a review of the literature

Abstract: Headache is one of the most common disorders in childhood, with an estimated 75% of children reporting significant headache by the age of 15 years. Pediatric migraine is the most frequent recurrent headache disorder, occurring in up to 28% of older teenagers. Headaches rank third among the illness-related causes of school absenteeism and result in substantial psychosocial impairment among pediatric patients.The aim of this study was to clarify the evolution of the clinical features of primary headache in the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
112
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(122 citation statements)
references
References 60 publications
4
112
1
5
Order By: Relevance
“…Both symptoms are a research field of its own and current reviews [e.g. 17,18] confirm what is known from studies on general PHC. Inconsistent time courses have not been attributed to possible inter-individual differences as yet.…”
mentioning
confidence: 54%
“…Both symptoms are a research field of its own and current reviews [e.g. 17,18] confirm what is known from studies on general PHC. Inconsistent time courses have not been attributed to possible inter-individual differences as yet.…”
mentioning
confidence: 54%
“…Migraine is a complex disease and the underlying mechanisms are not completely understood. While there is a clear neurophysiological/biological substrate of pain, the exact nature of the relationship between pain and psychological factors remains unclear . In pediatric population, headache phenotype (severity and clinical characteristics) can be influenced by psychological symptoms, such as anxiety and depression, and stressful life events have been frequently implicated in the onset, exacerbation, and maintenance of headache .…”
Section: Introductionmentioning
confidence: 99%
“…Seventy‐five percent of children report infrequent tension‐type headache or migraine by the age of 15 (Antonaci et al, ) with rates of headaches in children and adolescents ranging from 8 to 83% (King et al, ). In a global review of headache data, Wöber‐Bingöl () found the overall prevalence of headaches to be 59.2% for girls and 49.3% for boys.…”
Section: Introductionmentioning
confidence: 99%